The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ecc.13742
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence and coping attitudes of breast cancer survivors

Abstract: Objective: This study aimed to determine the fear of cancer recurrence levels and coping orientation of breast cancer survivors.Methods: This descriptive exploratory study was conducted using a web-based online survey. This article is written using the STROBE checklist. The study was completed with 204 women participants. Data were collected using the 'Demographic and Clinical Information Form', 'Fear of Cancer Recurrence Inventory (FCRI)' and 'Coping Orientation to Problems Experienced Inventory-Revised (COPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Additionally, the presence of maladaptive coping techniques was indicative of increased fear of progression and depression. Similarly, in a previous study of patients with breast cancer, it was reported that fear of progression was associated with maladaptive coping strategies, such as avoidance and self-punishment [ 10 ]. Fear of progression in cancer patients was predicted by viral anxiety, depression, and/or catastrophizing, as a maladaptive coping strategy.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Additionally, the presence of maladaptive coping techniques was indicative of increased fear of progression and depression. Similarly, in a previous study of patients with breast cancer, it was reported that fear of progression was associated with maladaptive coping strategies, such as avoidance and self-punishment [ 10 ]. Fear of progression in cancer patients was predicted by viral anxiety, depression, and/or catastrophizing, as a maladaptive coping strategy.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in a previous study of patients with breast cancer, it was reported that fear of progression was associated with maladaptive coping strategies, such as avoidance and self-punishment. 10 Fear of progression in cancer patients was predicted by viral anxiety, depression, and/or catastrophizing, as a maladaptive coping strategy. We did not include, in the present study, whether or not a patient's treatment schedule had been delayed as a confounding variable in the mediation model, since the proportion of delayed patients is low (4.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate fear facilitates patient monitoring for signs of relapse and promotes active treatment and healthy behaviors ( Hawkins et al, 2010 ; Cincidda et al, 2022 ). In contrast, excessive fear not only causes negative coping ( Oztas et al, 2022 ), exacerbates psychological distress, and reduces quality of life ( Cincidda et al, 2022 ), but may also increase the incidence of adverse drug reactions ( Lu et al, 2023 ), prompting patients to over-seek medical care and increasing health care costs ( Otto et al, 2018 ). In the long-term follow-up of cancer patients, dealing with FCR is one of the most frequently mentioned unmet needs of many patients after surgery ( Dahl et al, 2013 ; Adashek et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%